Rasionalitas Penggunaan Antibiotik pada Pasien Pneumonia di Salah Satu Rumah Sakit di Sumatera Barat - Lola Azyenela; Almahdy Almahdy; Vella Syafitri (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Pneumonia is an infectious disease or acute inflammation of the lung parenchyma, mainly caused by the bacteria Streptococcus pneumoniae. The use of antibiotics is the main therapy in the treatment of pneumonia, antibiotics used can inhibit the growth or kill the bacteria that cause infection. Irational use of antibiotics can cause treatment to be less effective, decreased drug safety, increased levels of resistance and increased treatment costs. The aim of this research is to examine the rationality of using antibiotics in pneumonia patients in the pulmonary inpatient installation of M. Zein Painan Hospital for the period January-December 2020. This type of research is non-experimental research, using descriptive methods and retrospective data collection, as well as data collection purposive sampling. Data were analyzed using reference sources in the form of Drug Pharmacotherapy Hand Book 11th Edition and Guidelines for Diagnosis & Management of Community Pneumonia in 2014. The results of this study were that there were 118 patients who were diagnosed with pneumonia in the pulmonary inpatient installation at M. Zein Painan Regional Hospital, and only 48 patients met the requirements. inclusion criteria.   The results of the rational analysis of antibiotic use showed that of the 48 pneumonia patients, the indication was correct as much as (100%), the patient was correct as much as (100%), the drug was correct as much as (95.84%), the dose was correct as much as (96.08%) and the duration was correct. giving as much as (92.16%). The conclusion is that there is still irrational use of antibiotics in the pulmonary inpatient installation at M. Zein Painan Regional Hospital.